2011
DOI: 10.1074/jbc.m110.182329
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid Reduces Amyloid β Production via Multiple Pleiotropic Mechanisms

Abstract: Alzheimer disease is characterized by accumulation of the ␤-amyloid peptide (A␤) generated by ␤-and ␥-secretase processing of the amyloid precursor protein (APP). The intake of the polyunsaturated fatty acid docosahexaenoic acid (DHA) has been associated with decreased amyloid deposition and a reduced risk in Alzheimer disease in several epidemiological trials; however, the exact underlying molecular mechanism remains to be elucidated. Here, we systematically investigate the effect of DHA on amyloidogenic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
155
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(169 citation statements)
references
References 84 publications
5
155
1
8
Order By: Relevance
“…Little is known about the incorporation of DHA-derived epoxides or diols into phospholipids, but this is highly likely given that the epoxides of arachidonic acid (the EETs) can be esterified to phosphatidylcholine, phosphatidylethanolamine, and phosphatidylinositols (Capdevila et al, 2000). This is not the first time a link between DHA and the -secretase has been reported, and although DHA increased -secretase activity in vascular smooth muscle cells (Delbosc et al, 2008), it was found to redistribute cholesterol out of lipid rafts Stillwell, 2008, 2009), thereby decreasing -secretase activity in a neuroblastoma cell line (Grimm et al, 2011 Adenovirus generation and Müller cell transduction. The human sEH (Ephx2) cDNA sequence, with a C-terminal Myc/His tag, was excised via NotI-PmeI from pcDNA3.1myc/His as previously described (BarbosaSicard et al, 2009) and cloned into the NotI-EoRV site of the cloning plasmid pAdTrackCMV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known about the incorporation of DHA-derived epoxides or diols into phospholipids, but this is highly likely given that the epoxides of arachidonic acid (the EETs) can be esterified to phosphatidylcholine, phosphatidylethanolamine, and phosphatidylinositols (Capdevila et al, 2000). This is not the first time a link between DHA and the -secretase has been reported, and although DHA increased -secretase activity in vascular smooth muscle cells (Delbosc et al, 2008), it was found to redistribute cholesterol out of lipid rafts Stillwell, 2008, 2009), thereby decreasing -secretase activity in a neuroblastoma cell line (Grimm et al, 2011 Adenovirus generation and Müller cell transduction. The human sEH (Ephx2) cDNA sequence, with a C-terminal Myc/His tag, was excised via NotI-PmeI from pcDNA3.1myc/His as previously described (BarbosaSicard et al, 2009) and cloned into the NotI-EoRV site of the cloning plasmid pAdTrackCMV.…”
Section: Methodsmentioning
confidence: 99%
“…19,20-DHDP is of particular interest, given that it was the most abundant lipid detected in the retinal lipid profile and that its precursor DPA has previously been reported to modulate the activity of the -secretase (Delbosc et al, 2008;Grimm et al, 2011). When activated, the -secretase cleaves the Notch intracellular domain (NICD), which then either undergoes rapid proteasome degradation or translocates to the nucleus and binds to transcription factors (Boulton et al, 2008).…”
Section: 20-dhdp and Notch Signalingmentioning
confidence: 99%
“…From plasma samples collected at 0, 3,7,10,15,20,40, and 60 minutes after infusion of [1-11 C]-DHA, total lipids were extracted into chloroform:methanol (1:1) as previously described [24].…”
Section: Input Functionmentioning
confidence: 99%
“…A combinação dos efeitos tóxicos de ambos, os agregados iniciais oligoméricos e o depósito de placas Aβ insolúveis, leva a um rompimento neuronal e a uma morte celular eventual, que por sua vez é responsável pelo declínio cognitivo irreversível encontrado na AD. 89,90 A riqueza dos dados coletados a partir de ensaios in vitro, em cultura celular e modelos de animais transgênicos para AD suporta uma associação direta de PUFAs ômega-3, principalmente DHA, com o processamento amiloide no cérebro. PUFAs ômega-3 como componentes integrais de membrana podem agir para alterar o processamento amiloidogênico de várias maneiras distintas incluindo: a) facilitar a interação de α-secretase com APP para produzir fragmentos não tóxicos e evitar a formação de Aβ; b) proteger a sequência de reconhecimento e sítio de clivagem intramembrana essencial para γ-secretase; c) servir como um local dissipador para os radicais livres que reduzem o aumento da atividade enzimática γ-secretase, que pode ser induzida por danos causados pelos radicais livres para o complexo de proteínas, o que é importante para a regulação da função normal γ-secretase e, d) inibir diretamente a fibrilação e formação de espécies oligoméricas de Aβ.…”
Section: Doença De Alzheimer (Ad)unclassified
“…Esses dados indicam que o DHA pode ter um efeito mais eficaz para prevenção do que para o tratamento dessa doença. 90 Estudos com cultura celular demonstraram consistentemente uma redução de 20% da produção de Aβ depois do tratamento com o DHA. 89,93,94 As atividades de ambas β-e γ-secretase estavam diminuídas quando essas culturas celulares foram tratadas com DHA, o que está de acordo com os níveis reduzidos de Aβ.…”
Section: Doença De Alzheimer (Ad)unclassified